Saúde e nutrição dos profissionais de saúde em unidades de hospitalares durante a pandemia da COVID-19: uma revisão integrativa - SILVA, Lorenna Vidal Rodrigues da (2023)
The SARS-CoV-2 virus gave rise to the COVID-19 pandemic, from the outbreak in the city of Wuhan, China, in 2019, giving rise to several research questions, and one of them is concern about the health of the health professionals during the pandemic period. Therefore, this integrative review sought to present the nutritional and health aspects related to these professionals during the pandemic. The review was carried out in six stages: 1. elaboration of the research question, 2. definition of the sources for the selection of primary studies and the inclusion and exclusion criteria, 3. definition and extraction of data, 4. evaluation of the included studies, 5 . critical analysis of the results, 6. presentation of the synthesis of the evidence found. With regard to health, which encompassed the quality of sleep, the practice of physical activities, the mental health and nutrition of health professionals, the studies analyzed suggest actions to promote and protect the mental health of professionals and point out the need for to better address this area, as well as to increase the incentive for a balanced and healthy diet, both in the hospital environment and at home, highlighting the importance of these areas for the maintenance of the well-being and health of the professional, and consequently for the delivering good results in the work environment.